Combination of Cyclic Steam Stimulation and Steam Flooding to Improve Oil Recovery in Unconsolidated Sand Heavy Oil Reservoir - Suranto, Ahmad Muraji; Swadesi, Boni; Widyaningsih, Indah; Widyaningsih, Ratna; Murni, Sri Wahyu; Alannafi, Lufis Alfian (Journal of Earth Energy Engineering, 2020)
Steam injection can be success in increasing oil recovery by determining the steam chamber growth. It will impact on the steam distribution and steam performance in covering hot areas in the reservoir. An injection plan and a proper cyclic steam stimulation (CSS) schedule are critical in predicting how steam chamber can grow and cover the heat area. A reservoir simulation model will be used to understand how CSS really impact in steam chamber generation and affect the oil recovery. This paper generates numerous scenarios to see how steam working in heavy oil system particularly in unconsolidated sand reservoir. Combine the CSS method and steam injection continue investigate in this research. We will validate the scenarios based on the how fast steam chest can grow and get maximum oil recovery. Reservoir simulation resulted how steam chest behavior in unconsolidated sand to improve oil recovery; It concluded that by combining CSS and Steam Injection, we may get a faster steam chest growth and higher oil recovery by 61.5% of heavy oil system.